The Islamic State We Knew Insights Before the Resurgence and Their Implications - Shatz, Howard J. (RAND Corporation, 2015)
This report provides information known by the end of 2011 about the Islamic State's origins, finances, organization, methods of establishing territorial control, and response to airpower. Countering the Islamic State can rely, in part, on the great deal of accumulated knowledge available. Iraqis and coalition forces routed the group once, and this history can inform the components of another successful strategy to defeat the Islamic State.